From "personal" to "interpersonal": a multilevel approach to uncovering the relationship between job satisfaction and knowledge sharing among IT professionals. Issue 6 (15th September 2021) - Lei, Yang; Zhou, Qiang; Ren, Jifan; Cui, Xiling
Abstract : Purpose: This study aims to examine how job satisfaction (JS) affects two types of knowledge sharing (KS), in-role KS and extra-role KS. It also investigates the mediating effect of knowledge sharing self-efficacy (KSSE) and the moderating effect of team collaborative culture (TCC) between JS and two types of KS. Design/methodology/approach: This study applies attribution theory to develop a cross-level model and validate it through paired data collected from 322 information technology professionals nested within 80 teams. Hierarchical linear modeling is used to test the hypotheses. Findings: JS positively influences in-role and extra-role KS via KSSE and TCC positively moderates the relationship between JS and extra-role KS. Originality/value: This study is one of the first to investigate the mechanism underlying the influence of JS on two types of KS. It also identifies the mediating and moderating effects of this mechanism.